Narrative Patterns and Cultural Transmission in Masbateños Urban Legends: A Framework for Controlled Shift Narration for Oral Tradition Preservation - Peritos, Cherry Marsh (Journal of Interdisciplinary Perspectives, 2025)
This research examines the transmission of stories across generations in Masbate City, Philippines, by analyzing the narrative patterns in local urban legends shared by 25 elder storytellers from five barangays. Working with community members aged 65 and above, the researcher collected and analyzed their oral narratives using a mixed-methods approach that combined qualitative content analysis with quantitative descriptive statistics. The study demonstrates that Masbateños consistently prefer straightforward, chronological storytelling, with linear narrative structures prevailing in their oral traditions (M = 2.8, SD = 0.84). Rather than employing nonlinear temporal structures, these storytellers consistently organize their legends in a sequential order that mirrors how events unfolded. The most intriguing discovery emerged from examining thematic relationships: a perfect negative correlation between origin and heroism narratives (ρ = -1.000, p < .001) suggests that these two story types serve entirely different functions within the community's oral tradition and operate in separate narrative spaces. This finding indicates that Masbateño communities have developed a sophisticated system for organizing their cultural knowledge, in which different thematic categories fulfil distinct pedagogical and mnemonic roles. However, the study also documented generational erosion, in which younger storytellers systematically omit cultural details and shift narrative perspectives, threatening the preservation of authentic cultural memory. In response to these preservation challenges, the researcher developed the Controlled Shift Narration (CSN) framework. This community-based intervention employs strategic perspective alignment, linguistic anchoring of vernacular terms, and pedagogical integration to maintain narrative authenticity while allowing natural evolution across generations. Unlike existing preservation models that prioritize static documentation, CSN acknowledges the inherently dynamic nature of oral tradition while providing structured mechanisms to mitigate unintentional distortion. This framework offers practical tools for cultural heritage preservation initiatives and contributes to folklore studies’ methodology by bridging the gap between authenticity and adaptability in oral narrative transmission.